Konsep Insan Kulli menurut Syed Muhammad Naquib al-Attas - Kholili Hasib (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This article is an analysis the concept of insān kullī according to Prof. Syed Muhammad Naquib al-Attas based on philosophy approach. In his thought’s, the concept of insān kullī (universal man) is one’s of basic elements of the worldview of Islam. Therefore, the concept of insān kullī is the one of most important thing at the Prof. Al-Atta’s thought. Through this approach, the writer find that the concept of insān kullī are related to the worldview, epistemology, and education. In the education aspect for, instant, the concept of insān kullī is like a symbol of Islamic university. The islamic university should reflected the universal man. The high education institutions must be chaired by an individual academic leader who has fardhu ‘ain science, requaired knowledge. And also committed to religious-philosophical and socio-cultural values in education which is called insan adabi. In addition, an understanding of insān kullī is studied from metaphyscila aspects of Islam. So, the concept of insān kullī is the basic of Islamic education. The main aims of islamic education are incalculate the insan adabi. So, the basic metaphysic of Islam must be main and basic element of Islamic education.